QUANTUM CHEMICAL DESCRIPTORS AND BIOLOGICAL ACTIVITY OF 2-AMINO-4-ARYL-1,3-OXAZOLES - Bondar Олена; Tarasenko Інна; Kurmakova Ірина; Makei Олександр (Biota. Human. Technology, 2025)
Purpose of the work. To calculate quantum chemical descriptors for 2-amino-4-aryl-1,3-oxazole derivatives, prediction of possible protein targets, and establishment of correlational dependencies of the type "biological activity - quantum-chemical descriptor". Methodology. The study was conducted using ChemOffice software packages (PerkinElmer Informatics Inc, 2018), ACDLabs (Advanced Chemistry Development Inc.), online resources Molinspiration Cheminformatics (Slovensky Grob, Slovakia https://molinspiration.com/cgi/properties), OSIRIS Property Explorer (Idorsia Pharmaceuticals Ltd, Switzerland Molecular Properties Prediction, https://www.organic-chemistry.org/prog/peo/), SwissTargetPrediction (SIB Swiss Institute of Bioinformatics, http://www. swisstargetprediction.ch/), SuperPred (Structural Bioinformatics Group, Institute of Physiology Charité-University Medicine, Berlin, https://prediction.charite.de/subpages/target_prediction.php), ProTox (Structural Bioinformatics Group, Institute of Physiology Charité-University Medicine, Berlin https://tox.charite.de/protox3). Microsoft Excel was used to perform correlation and regression analyses in the coordinates of binding probability - quantum chemical descriptors. Scientific novelty. Were evaluated the pharmacological activity of new 2-amino-4-aryl-1,3-oxazole derivatives and identified correlations between the probability of their effectiveness and the quantum chemical parameters of the molecules. Conclusions. Several correlations have been established for the probable ligands, focusing on those with the highest binding probability as well as various quantum chemical descriptors, including the charges on oxygen and nitrogen atoms and the energies of the highest occupied and lowest vacant molecular orbitals. The results obtained are valuable for making more informed predictions about the biological activity of new 2-amino-4-aryl-1,3-oxazole derivatives and for guiding the synthesis of promising dosage forms.